The Effectiveness of Modified Long Clogs Traditional Game on Gross Motor Skills of Early Childhood 4-6 Years Old - Ilaika Al Quratu Aini; Fauzi Shaputra Husin; Berlian Agatha Silalahi; Muhamad Arief Setiawan (Journal of Physical Education Health and Sport, 2025)
This study aims to determine the effectiveness of the modified traditional long clog game on improving gross motor skills in early childhood. The study used a quasi-experimental method with a One Group Pretest–Posttest Design. The subjects were 12 children in Group A at Putra Pertiwi Kindergarten, Bekasi Regency, selected by purposive sampling. Data were obtained through observations of children’s gross motor skills using five main indicators: balance, leg muscle strength, coordination, social, and emotional. The analysis results using the paired sample t-test showed a significance value of 0.000 < 0.05 and t_count 9.58 > t_table 2.20, which means there is a significant difference between the pretest and posttest results. These findings indicate that the modified long clogs game effectively improves the gross motor skills of children aged 4–6 years. This activity not only strengthens motor coordination and body balance, but also trains children’s cooperation, focus, courage, and social-emotional abilities. In addition to providing physical benefits, this game contributes to character building through fun and educational play activities. Thus, the modified long clogs game is worthy of being integrated into the Early Childhood Education (PAUD) curriculum as a local culture-based learning medium that is able to develop children’s physical, social, and emotional aspects comprehensively.